2012
DOI: 10.1007/s00244-012-9768-1
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Concentration in the Spectacled Caiman and Black Caiman (Alligatoridae) of the Amazon: Implications for Human Health

Abstract: Mercury (Hg) concentrations in the Amazon are generally high, but no studies have been published on Hg concentrations in caimans (Alligatoridae) from the region. Aiming for sizes representative of caimans traded for food in the Amazon, we measured Hg concentration in tail muscle of spectacled caiman (Caiman crocodilus crocodilus) and black caiman (Melanosuchus niger) from the Purus River basin. The information on Hg concentration in caimans from this area is important because of the potential health risk to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 46 publications
(57 reference statements)
4
33
0
Order By: Relevance
“…2), it is important to note that the variation of the concentrations in scute of males is higher than the variation in females. Similar findings were previously reported in different tissues of M. niger (Schneider et al, 2012), but contradictory results were found in A. mississipiensis with higher Hg concentrations in males than in females, since the latter ones are able to reduce their body burden of Hg when eggs are laid (Delany et al, 1988).…”
Section: Relationship Of Hg Concentrations In Tissues To Animal Size supporting
confidence: 86%
See 3 more Smart Citations
“…2), it is important to note that the variation of the concentrations in scute of males is higher than the variation in females. Similar findings were previously reported in different tissues of M. niger (Schneider et al, 2012), but contradictory results were found in A. mississipiensis with higher Hg concentrations in males than in females, since the latter ones are able to reduce their body burden of Hg when eggs are laid (Delany et al, 1988).…”
Section: Relationship Of Hg Concentrations In Tissues To Animal Size supporting
confidence: 86%
“…There are several works showing that Hg in crocodilians muscles increases linearly with time of exposure (Yanochko et al, 1997;Burger et al, 2000;Rumbold et al, 2002;Schneider et al, 2012) but few have examined the relationship between size and Hg concentration in keratinized tissues (Schneider et al, 2015). Previous studies have reported a significant positive correlation between Hg concentration in scute and size in A. mississipiensis, M. niger and C. crocodilus (Yanochko et al, 1997;Burger et al, 2000;Schneider et al, 2015) but not in C. moreletii and C. acutus (Rainwater et al, 2002).…”
Section: Relationship Of Hg Concentrations In Tissues To Animal Size mentioning
confidence: 93%
See 2 more Smart Citations
“…Crocodiles and alligators are known for their longest life span, and during their lives, they encounter numerous pathogenic microbes, toxicants, pollutants, carcinogens etc. but thrive in these conditions . The serum of the Siamese crocodile ( Crocodylus siamensis ) was purified to separate antibacterial agents and found to be active against several bacterial pathogens including Salmonella typhi , E. coli , S. aureus , S. epidermidis , K. pneumoniae , P. aeruginosa and Vibrio chorelae .…”
Section: Animal‐based Antimicrobial Discovery: a Largely Untapped Soumentioning
confidence: 99%